Features of the Entrepreneurial University Model - DURIKHINA, O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
The article considers the main approaches to the definition of the concept of “entrepreneurial university”, identifies the features of research and entrepreneurial activities in higher education institutions, the main problems of entrepreneurial university development. The main features of entrepreneurial universities are described on the example of the U.S. The main problems in the formation of entrepreneurial universities are identified. The global experience of entrepreneurial university formation is analyzed from the perspective of creating and developing entrepreneurial universities in Ukraine. In the context of globalization of educational systems, increasing competition on the market of educational services, increasing requirements for the provision of educational services faced by educational institutions, there is a need to change and transform the paradigm of university behavior. The governments of many countries around the world are trying to move away from direct state funding for the education sector and attract support of investors and businesses. When exploring the structure of the global education area, it is important to emphasize that it is a complex and open system that is constantly transforming and evolving. The increasing competition between universities and countries has direct impact on ways and solutions aiming to expand the boundaries of their activities.